Visceral Adiposity Index Plays an Important Role in Prognostic Prediction in Patients With Non-ST-Segment Elevation Acute Coronary Syndrome and Type 2 Diabetes Mellitus Undergoing Percutaneous Coronary Intervention - Zhao, Qi; Cheng, Yu-Jing; Xu, Ying-Kai; Zhao, Zi-Wei; Liu, Chi; Sun, Tie-Nan; Zhou, Yu-Jie (Frontiers in Cardiovascular Medicine, 2021)
Background: Visceral adiposity index (VAI), a surrogate marker of adiposity and insulin resistance, has been demonstrated to be significantly related to cardiovascular disease. It remains indistinct whether VAI predicts adverse prognosis after percutaneous coronary intervention (PCI) for patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) and type 2 diabetes mellitus (T2DM). Methods: 798 participants who met the enrollment criteria were finally brought into this study. VAI was determined by waist circumference, body mass index, fasting triglyceride, and high-density lipoprotein cholesterol as previously reported. Adverse prognosis included all-cause death, non-fatal myocardial infarction, non-fatal ischemic stroke, and ischemia-driven revascularization, the composite of which was defined as the primary endpoint. Results: Higher VAI maintained as a significant and independent risk predictor for the primary endpoint, regardless of the adjustment for various multivariate models [Hazard ratio (95% confidence interval) for fully adjusted model: 2.723 (2.015-3.680), P < 0.001]. The predictive value of VAI was further confirmed in sensitivity analysis where VAI was taken as a continuous variate. There was a dose-response relationship of VAI with the risk of the primary endpoint (P for overall association < 0.001). Moreover, the ability of VAI on the prediction of the primary endpoint was consistent between subgroups stratified by potential confounding factors (all P for interaction > 0.05). VAI exhibited a significant incremental effect on risk stratification for the primary endpoint beyond existing risk scores, expressed as increased Harrell’s C-index, significant continuous net reclassification improvement, and significant integrated discrimination improvement. Conclusion: VAI is a significant indicator for predicting worse prognosis and plays important role in risk stratification among patients with NSTE-ACS and T2DM undergoing elective PCI. The present findings require further large-scale, prospective studies to confirm.